Prevalência e características do tabagismo na população universitária da região de Lins-SP - Almeida, Janaina Benatti De; Miranda, Jéssica Steffany [UNESP]; Miyasaki, Sandra Cristina Shiguemi; Marques, Silvio Fernando Guideti (Associação Brasileira de Enfermagem, 2011)
The study aimed to know the prevalence of smoking and to describe the profile and smoking habits of undergraduate students of Lins-SP. A sample of 368 undergraduate students answered a questionnaire with questions directed at smokers, ex-smokers and nonsmokers The prevalence of smoking was of 11,7%; about 85,3% of the students were nonsmokers and 4,0% were classified as ex-smokers. Of the students interviewed, 54,1% were women. It was noted that the average use was from 5,1 to 5,4 cigarettes per day, and that the students used industrialized cigarettes. This index of prevalence correlates to the ones of others University Centers and demands politics of smoking control among the university environment.

El estudio tuvo como objetivo conocer la prevalencia del tabaquismo y describir el perfil y hábitos de tabaquismo entre estudiantes universitarios de Lins-SP. Una muestra de 368 estudiantes respondieron a un cuestionario con preguntas dirigidas a fumadores, ex fumadores y no fumadores. La prevalencia de tabaquismo fue de 11,7%; 85,3% de los estudiantes eran no fumadores y 4,0% fueron clasificados como ex fumadores. Entre los encuestados, el 54,1% eran mujeres. Fue observado un consumo medio de 5,1 ± 5,4 cigarrillos por día, y todos los estudiantes fumadores utilizaban cigarrillos comerciales. Esta tasa de prevalencia es similar a otros centros universitarios y demanda políticas de control del tabaco en los círculos universitarios.

O estudo objetivou conhecer a prevalência do tabagismo e descrever o perfil e hábitos tabágicos entre universitários de Lins-SP. Uma amostra de 368 alunos respondeu a um questionário com perguntas dirigidas a fumantes, ex-fumantes e não fumantes. A prevalência de tabagismo foi de 11,7%; 85,3% dos alunos não eram fumantes e 4,0% foram classificados como ex-fumantes. Do total de alunos entrevistados, 54,1% eram mulheres. Foi observado consumo médio de 5,1 ± 5,4 cigarros por dia, sendo que todos os universitários tabagistas utilizavam o cigarro industrializado. Este índice de prevalência assemelha-se aos de outros Centros Universitários e demanda políticas de controle do tabagismo nos meios universitários.
Prevalence and smoking characteristics in the university population of the region of Lins-SP
Predominio y características del tabaquismo en la población universitaria de la región de Lins-SP
Keywords: Smoking; Smoking habits; Epidemiology; Health policy; Tabagismo; Hábito de fumar; Epidemiologia; Política de saúde